Coronavirus Disease 2019 (COVID-19): Impending Encounters for Dental Health Professionals in India - Ramesh Nagarajappa1 , Debasruti Naik2 , Gayathri Ramesh3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Originating in Wuhan, China, the epidemic of coronavirus disease 2019 (COVID-19) has become a majorpublic health challenge for not only China but also countries around the world. The outbreaks of the novelcoronavirus have constituted a public health emergency of international concern as announced by the WorldHealth Organization (WHO). For dental care provision to active or suspected COVID-19 cases, no universalprotocol or guideline is available till date. Major challenges to worldwide health systems will have farreaching consequences on the global economy if the spread of the virus is not effectively controlled as aconsequence of the COVID-19 outbreak. So, in a nutshell, there is no point in being cynical about the futureof the dental profession.